Comparing Literatures: Aspects, Method, and Orientation Proceedings of the 8th Congress of the European Society of Comparative Literature (ESCL-SELC) - Boulanger, Alison; McIntosh-Varjabédian, Fiona
Globalization is not a new phenomenon. Ideas have been circulating all over Europe (and the world) since ancient times, and intercultural dialog is a wide field offering a great variety of approaches. In such times as ours, when the world is swift to change and cultures are destined to meet (sometimes, alas, to clash), the place of literature, or broadly speaking: human and social sciences, within society is often questioned and needs redefining: From the reception studies of the 1970s and 1980s to the stress laid on intermedial and intercultural relations, not forgetting the work done on cultural transfers, this question opens up a wide field of theoretic, methodological, and aesthetic research, which is explored through this volume